The association between training load and physical development in professional male youth soccer players: a systematic review - Rice, J.; Brownlee, T. E.; McRobert, A. P.; Ade, J.; Drust, B.; Malone, J. J. (International Journal of Sports Science & Coaching, 2022)
Objectives 1) To evaluate current physical performance tests used within professional male youth soccer; 2) to understand the relationship of these tests performance in relation to specific measures of external and internal training load (TL) to conclude if there is a subsequent change in test performance.